Modeling of EBV Infection and Antibody Responses in Kenyan Infants With Different Levels of Malaria Exposure Shows Maternal Antibody Decay is a Major Determinant of Early EBV Infection. (28th August 2016) - Reynaldi, Arnold; Schlub, Timothy E.; Piriou, Erwan; Ogolla, Sidney; Sumba, Odada P.; Moormann, Ann M.; Rochford, Rosemary; Davenport, Miles P.
Abstract: The combination of Epstein-Barr virus (EBV) infection and high malaria exposure are risk factors for endemic Burkitt lymphoma, and evidence suggests that infants in regions of high malaria exposure have earlier EBV infection and increased EBV reactivation. In this study we analyzed the longitudinal antibody response to EBV in Kenyan infants with different levels of malaria exposure. We found that high malaria exposure was associated with a faster decline of maternally derived immunoglobulin G antibody to both the EBV viral capsid antigen and EBV nuclear antigen, followed by a more rapid rise in antibody response to EBV antigens in children from the high-malaria-transmission region. We also observed the long-term persistence of anti–viral capsid antigen immunoglobulin M responses in children from the high-malaria region. More rapid decay of maternal antibodies was a major predictor of EBV infection outcome, because decay predicted time to EBV DNA detection, independent of high or low malaria exposure.